Lactic acid bacteria as a biopreservative in fermented foods / Fatin Fatanah Ruslan and Safiyyah Shahimi - Ruslan, Fatin Fatanah; Shahimi, Safiyyah (2021)
Public concerns regarding the safety of chemical preservatives in food have led to the use of natural preservatives. Naturally produced antimicrobial compounds tend to promote the substitution of conventional methods and lessen the rigidity of the use of chemical and physical preservatives. In this review, the effects of lactic acid bacteria (LAB) metabolites on the shelf life of fermented foods were investigated. Analysis of the LAB antimicrobial activity against pathogenic bacteria and the effect of LAB on physicochemical properties of the fermented foods were done. Based on the relevant articles, the shelf life of the fermented food was increased with the presence of LAB metabolites including lactic acid, acetic acid, sorbic acid, benzoic acid and bacteriocin. The LAB was found to be able to replace chemical preservatives as the shelf life of food samples was extended. Moreover, no negative effect was reported on the physicochemical properties of fermented food from the addition of LAB. It was shown to inhibit pathogenic bacteria Listeria monocytogenes, Bacillus subtilis, Escherichia coli, Salmonella typhimurium, Staphylococcus aureus and Micrococcus luteus with the most dominant species of Lactobacillus plantarum found. Hence, these findings have demonstrated the LAB as an efficient biopreservative in fermented foods.